Children's hospital quality ratings: where are we and can we do better?. Issue 1 (13th October 2021) - Chaulk, David; Tran, Theresa; Neeley, Allison; Giardino, Angelo
ABSTRACT: Objective: Hospital quality ratings are intended to guide patients and payers to the highest quality hospitals. Their success in achieving this goal has been limited by inconsistencies between ratings and questionable data collection methods. Despite these shortcomings, their popularity and importance are increasing. The purpose of this review is to identify the strengths and weaknesses of the US News and World Report (USNWR) Best Children's Hospitals Report and Leapfrog Pediatric Care Survey and discuss improvement opportunities. Methods: A structured literature review was performed analyzing hospital quality surveys. Previously published criteria were used to compare the USNWR Best Children's Hospitals Report and Leapfrog Pediatric Care Survey. Results: This narrative review highlights the strengths and weakness of both the USNWR Best Children's Hospitals Report and the Leapfrog Pediatric Care Survey, including a letter grade comparison. Conclusion: Existing children's hospital rating systems are lacking. We suggest specific improvements that may better enable these reports to influence the quality of pediatric care.